Ethnozoology in Brazil: current status and perspectives - Alves Rômulo RN; Souto Wedson MS (Journal of Ethnobiology and Ethnomedicine, 2011)
Abstract Ancient connections between animals and human are seen in cultures throughout the world in multiple forms of interaction with the local fauna that form the core of Ethnozoology. Historically, ethnozoological publications grew out of studies undertaken in academic areas such as zoology, human ecology, sociology and anthropology - reflecting the interdisciplinary character of this discipline. The rich fauna and cultural diversity found in Brazil, with many different species of animals being used for an extremely wide diversity of purposes by Amerindian societies (as well as the descendents of the original European colonists and African slaves), presents an excellent backdrop for examining the relationships that exist between humans and other animals. This work presents a historical view of ethnozoological research in Brazil and examines its evolution, tendencies, and future perspectives. In summary, literature researches indicated that ethnozoology experienced significant advances in recent years in Brazil, although from a qualitative point of view improvement is still needed in terms of methodological procedures, taxonomic precision, and the use of quantitative techniques. A wide range of methodologies and theories are available in different areas of learning that can be put to good use in ethnozoological approaches if the right questions are asked. The challenges to studying ethnozoology in Brazil are not insignificant, and the tendencies described in the present study may aid in defining research strategies that will maintain the quantitative growth observed in the recent years but likewise foster needed qualitative improvements.